Callithrix penicillata como um modelo primata para o estudo da infecção por isolado humano de Strongyloides stercoralis - Vitor Luis Tenorio Mati (2013)
Advances in experimental strongyloidiasis have been limited, at least in part, due to the lack of an easy to handle, small and viable animal model for the study and maintenance in the laboratory of Strongyloides stercoralis. In order to obtain a susceptible model to the human parasite, Callithrix penicillata (n = 15) were infected by subcutaneous route with 100 (n = 4), 300 (n = 2) or 500 (n = 9) infective third-stage larvae (L3i) of S. stercoralis. When the infection was already established, 3 marmosets (2 infected with 100 and one with 300 L3i) were treated with dexamethasone (DEX) (2.5 mg/Kg/day) for 5 consecutive days. Quantitative and qualitative analysis of S. stercoralis larvae excreted in feces of primates were performed. Dead primates were necropsied and parasitic forms recovered. Tissue fragments were collected and processed for histopathology. Specimens of C. penicillata were susceptible, and no difference was usually observed in the course of infection between marmosets that had received different numbers of L3i. The prepatent and patent periods were, respectively, 16.1 ± 3.0 and 161.1 ± 72.2 days post-infection (DPI). Between the 15th and 35th DPI the highest values of larvae/g of feces were found. In general, the infection was well tolerated by primates, but those individuals who received DEX showed progressive clinical deterioration and died of disseminated infection. In these cases, an amount of adult females higher than the number of L3i inoculated was recovered, and a large amount of larvae migrating through the host tissues was observed. Anatomopathological findings in complicated and uncomplicated forms of experimental strongyloidiasis were variables and consistents with previous observations regarding the human strongyloidiasis, having occurred mild cases of catarrhal enteritis and severe conditions, especially in disseminated infection, with ulcerative enteritis, edematous colitis and diverse lung injuries, including hemorrhage, bronchopneumonitis, thromboembolism and infarction. The data obtained indicate that the experimental infection of C. penicillata with S. stercoralis is representative of human infection, including severe disease, and the maintenance of the cycle of the parasite in the laboratory is possible in this host. Additionally, aspects of the biology of the nematode and pathogenesis, which are still objects of controversies in the literature, were discussed based on new information obtained in the proposed primate model.